Scribal laws: exegetical variation in the textual transmission of biblical law in the late second temple period - Teeter, Andrew (Forschungen zum Alten Testament, 2014)
On the basis of a detailed analysis of extant texts and versions, David Andrew Teeter examines the nature and background of deliberate scribal changes in the text of biblical law during the late Second Temple period. What were the "laws" governing this mode of scribal production and how are the "laws" produced thereby to be understood? What are the underlying causes of textual difference, and what are the effects of the resulting plurality upon the character of interpretive scriptural encounter? What do the attested textual differences reveal about the social history of the biblical text, and